Understanding Emergency Department Healthcare Professionals' Perspectives of Caring for Individuals in Suicidal Crisis: A Qualitative Study - Rheinberger, Demee; Wang, Jessica; McGillivray, Lauren; Shand, Fiona; Torok, Michelle; Maple, Myfanwy; Wayland, Sarah (Frontiers in Psychiatry, 2022)
Help seekers regularly present to Emergency Departments (EDs) when in suicidal crisis for intervention to ensure their immediate safety, which may assist in reducing future attempts. The emergency health workforce have unique insights that can inform suicide prevention efforts during this critical junction in an individual’s experience with suicide. This paper explores the treatment and care delivery experiences of 54 health professionals working in EDs within one of the LifeSpan suicide prevention trial sites in Australia. Data was collected via six focus groups and six interviews. Thematic analysis resulted in three themes: 1) physicality of the emergency department, 2) juggling it all – the bureaucracy, practicalities, and human approach to care, and 3) impact of care delivery on ED staff. Findings highlight the need for workplace training that incorporates responding to the uncertainty of suicidal crisis, to compliment the solution-focused medical model of care. Broader policy changes to the ED system are also considered to ensure better outcomes for health professionals and help-seekers alike.